Astaxanthin improves serum cytokine expression and semen quality of diabetes mellitus KKAy mice. (1st December 2020) - Hao, Zhiqiang
Abstract: The present study aims to explore the effects of astaxanthin on the semen quality of diabetes mellitus (DM) KKAy mice. A total of 60 DM KKAy mice with similar body weights and initial blood glucose and serum lipid levels were assigned to four groups, namely, one control and three astaxanthin treatments (10, 50, or 100 mg/kg astaxanthin). Results show that oral astaxanthin administration reduced fasting blood glucose and serum total cholesterol, low-density lipoprotein cholesterol, insulin and nitrate oxide levels in the testis of DM KKAy mice. Astaxanthin also improved the high-density lipoprotein cholesterol, protein and superoxide dismutase levels in the testis; serum interleukin-11, tumour necrosis factor-α and interferon-γ levels; and sperm density, sperm movement and normal morphology rate of DM KKAy mice. Based on the results, astaxanthin can effectively affect serum cytokines and ameliorate semen quality of DM KKAy mice; thus, it may be developed as an adjuvant drug to treat diabetes mellitus-induced infertility. Highlights: Astaxanthin decreased fasting blood glucose of diabetes mellitus KKAy mice. Astaxanthin decreased serum lipid levels of diabetes mellitus KKAy mice. Astaxanthin improved sperm quality of diabetes mellitus KKAy mice.